Nanoparticle surface coatings produce distinct antibacterial effects that are consistent across diverse bacterial species - Ameh, Thelma; Zarzosa, Kuzy; Braswell, W. Evan; Sayes, Christie M. (Frontiers in Toxicology, 2023)
Nanoparticles have been proposed as tunable delivery vehicles for targeted treatments and, in some cases, the active therapeutic agents themselves. Despite the promise of such customizable impacts, little evidence exists to support these claims in the realm of antibiotics. Exploration of the silver and copper nanoparticle antibacterial impacts have been reported with inconsistent results. Here, we investigate the physical, chemical, and bacterial properties of silver and copper core particles stabilized with organic ligand shells to confer negative, neutral, and positive surfaces charges. The impacts of these potential antibacterial nanoparticles are measured against three bacterial species spanning deep divisions in the bacterial tree of life and include Escherichia coli, Staphylococcus aureus, and Sphingobacterium multivorum. Varying dose, core composition, organic ligand shell, and bacterial species revealed that nanoparticle surfaces accounted for most of the variation in antibacterial activity. In all experiments, dose produced a linear inhibitory effect. Surprisingly, bacterial species reacted similarly regardless of evolutionary relatedness. There is a high degree of consistency, effectiveness, and efficacy among neutrally charged silver and copper nanoparticle surfaces. These findings have implications for the intentional use of nanotechnology in environmental systems.